Correlation Between Tax Policy and Corruption in the Legal Perspective for Country's Economic Growth - Gideon J.; Edgar H.; Ivan; Nabil; Aptina; Nadia P.; Dewi R. (Hang Tuah Law Journal, 2017)
People Tax is the main source of state income. The better the tax policy of a country, the better the development of a country. One of the factors that influence the level of public awareness in paying taxes is corruption. Study shows that tax collection is one of them influenced by corruption. In the data of Corruption Perceptions Index 2016 reported by Transparency International, Indonesia is ranked 90 out of 176 countries. Tax evasion is a serious problem for many countries. Every year, the government loses revenue potential as many residents evade taxes in various ways. For this reason, the government implements tax amnesty. Tax amnesty is designed to permanently reduce the amount of underground economy activity, thereby increasing tax revenues in the future and developing countries can grow well.